Searching for the History of the Ancient Basilicata: Archaeogeophysics Applied to the Roman Site of Forentum - Luigi Capozzoli; Sabrina Mutino; Maria Grazia Liseno; Gregory De Martino (Heritage, 2019)
This paper describes the results obtained using an archaeogeophysical-based approach for discovering new Roman structures belonging to the ancient settlement of Forentum, currently identifiable by a well-preserved sanctuary from the third century BC. The investigated area has been affected by invasive anthropic activities that have partially damaged the Roman structures. Extensive geophysical measurements, including detailed ground-penetrating radar investigations supported by magnetometric data, have allowed for the identification of an impressive complex of structures composed of various buildings. Magnetometric and electromagnetic anomalies suggest the existence of an “urban” dimension close to the Gravetta Sanctuary, totally unearthed and unknown until now, organized into regular patterns in a similar way to the most famous site in the vicinity of Bantia, or the famous Apulian archaeological sites of Ordona and Arpi.